Epidemiology and Outcomes in Critically Ill Patients with Human Immunodeficiency Virus Infection in the Era of Combination Antiretroviral Therapy. (27th February 2017) - Turvey, Shannon L.; Bagshaw, Sean M.; Eurich, Dean T.; Sligl, Wendy I.
Abstract : Purpose. The impact of critical illness on survival of HIV-infected patients in the era of antiretroviral therapy remains uncertain. We describe the epidemiology of critical illness in this population and identify predictors of mortality. Materials and Methods. Retrospective cohort of HIV-infected patients was admitted to intensive care from 2002 to 2014. Patient sociodemographics, comorbidities, case-mix, illness severity, and 30-day mortality were captured. Multivariable Cox regression analyses were performed to identify predictors of mortality. Results. Of 282 patients, mean age was 44 years (SD 10) and 169 (59%) were male. Median (IQR) CD4 count and plasma viral load (PVL) were 125 cells/mm 3 (30–300) and 28, 000 copies/mL (110–270, 000). Fifty-five (20%) patients died within 30 days. Factors independently associated with mortality included APACHE II score (adjusted hazard ratio [aHR] 1.12; 95% CI 1.08–1.16; p < 0.001 ), cirrhosis (aHR 2.30; 95% CI 1.12–4.73; p = 0.024 ), coronary artery disease (aHR 6.98; 95% CI 2.20–22.13; p = 0.001 ), and duration of HIV infection (aHR 1.07 per year; 95% CI 1.02–1.13; p = 0.01 ). CD4 count and PVL were not associated with mortality. Conclusions. Mortality from an episode of critical illness in HIV-infected patients remains high but appears to be driven by acute illness severity and HIV-unrelated comorbid disease rather than degree of immune suppression.